Third body perturbation using a single averaged model considering elliptic orbits for the disturbing body - Domingos, Rita De C. [UNESP]; De Moraes, Rodolpho V. [UNESP]; De Almeida Prado, A. F.B. (My University, 2008)
In the present work, we expanded the study done by Solorzano1 including the eccentricity of the perturbing body. The assumptions used to develop the single-averaged analytical model are the same ones of the restricted elliptic three-body problem. The disturbing function was expanded in Legendre polynomials up to fourth-order. After that, the equations of motion are obtained from the planetary equations and we performed a set of numerical simulations. Different initial eccentricities for the perturbing and perturbed body are considered. The results obtained perform an analysis of the stability of a near-circular orbits and investigate under which conditions this orbit remain near-circular.